Chinese Aid and Democratic Values in Latin America - Andreas Freytag; Miriam Kautz (Center for Economic Studies and ifo Institute (CESifo), 2022)
International economic engagement has been increasingly framed in terms of liberal democratic values. Specifically, Chinese aid has been at the center of this debate. Since Chinese aid comes with "no strings attached," a popular narrative is that Chinese aid poses a challenge to conditional aid, thus weakening democracy promotion. This study aims to deepen our understanding of how democratic values are shaped by international economic engagement. Drawing on the Latinobarómetro Household Survey, we use an instrumental variable approach to test the effect of Chinese aid on attitudes toward democracy in 18 Latin American countries on the national and regional level. We find that Chinese aid has a non-negative effect on support for democracy. We also find that individuals who have a positive attitude towards China are more likely to value democracy. In contrast, positive attitudes towards the USA have no robust impact on support for democracy.
Keywords: F35; F61; F69; O54; P33; 330; China; Latin America; foreign aid; public opinion; support for democracy; values